Caliph on Earth: Ecological Responsibility in the Hadith of the Prophet Muhammad SAW (Study of Sanad and Matan) - Hamzah, Ghufron (LP. Ma'arif Janggan Magetan, 2024)
The global ecological crisis demands a strong spiritual perspective to drive a change in human behavior toward the environment. This article examines the concept of caliph (earth manager) in Islam through the analysis of 12 categories of hadith of the Prophet Muhammad SAW that are relevant to ecological issues, including water conservation, protection of flora and fauna, prohibition of waste, environmental cleanliness, and principles of sustainability. Using the method of takhrij hadith and sanad-matan analysis, this study identifies and evaluates the quality of ecological hadiths (sahih and hasan) and their implications for human responsibilities as caliphs. The results of the study show that the Prophet Muhammad SAW has provided comprehensive guidance on environmental management, emphasizing that ecological responsibility is not only a worldly obligation but also worship that will be accounted for in the hereafter. This research confirms that the revitalization of prophetic teachings on ecology can be an alternative solution in dealing with contemporary environmental crises, by integrating spiritual, ethical, and practical dimensions in natural resource management.